Women's Behavioral Responses to Sexual Aggression: The Role of Secondary Cognitive Appraisals and Self-Regulation. (December 2017) - Tirabassi, Christine K.; Caraway, S. Jean; Simons, Raluca M.
Sexual assault history, secondary cognitive appraisals, and a dual-process model of self-regulation were examined as predictors of women's intended behavioral responses to hypothetical sexual aggression. College women ( N = 435) read a sexually aggressive scenario and rated their intentions to engage in assertive, polite, and passive behavioral responses. Results indicated secondary cognitive appraisals predicted less assertive, more polite, and more passive responses. Good self-control predicted assertive and polite responses, while sexual assault history and poor regulation predicted passive responses. Poor regulation significantly moderated the relationship between secondary cognitive appraisals and passive behavioral responses. Implications for the prevention of sexual assault are discussed.